Backscatter Measurements of Sea Ice with a Helicopter-Borne Scatterometer. - Patel ,J S; Onstott ,R G; Delker ,C V; Moore,R K (1979)
The purpose of this paper is to describe the design and development of the University of Kansas helicopter-borne scatterometer system, HELOSCAT. The experiments performed to measure the radar backscatter from sea ice with this system along with the results are also described. Backscatter measurements were made at 1-2 GHz and 8-18 GHz frequencies, HH-polarization, and three incidence angles (20, 40, and 60 deg). Different types of ice ranging from thin ice to multiyear ice were observed; however, most data were collected from thick first-year and multiyear ice. A comparison of 1-2 GHz results for thick first-year and multiyear ice shows that the scattering coefficient values for multiyear ice at 60 deg are slightly lower than the value for thick first-year ice. The 8-18 GHz results show that the backscatter from multiyear ice at these frequencies is higher than the backscatter return from thick first-year ice by at least 3-4 dB. The frequency response of backscatter return is an upward sloping straight line on a dB-vs-frequency plot. For the multiyear ice, only the 60 deg data was found usable; the data at 20 deg and 40 deg were determined to be erroneous because of a malfunctioning frequency counter.